Decision-Making Methods in the Public Sector during 2010–2020: A Systematic Review - Fountzoula, Christina; Aravossis, Konstantinos (Advances in Operations Research, 2022)
The aim of this article is to analyze the scientific developments in public sector decision making during the period 2010–2020, to identify which decision-making methods are preferred in different sectors of the public sector, and to determine which integrated methods are applied in this sector. In total, 468 scholarly articles were selected covering a near comprehensive review of the literature, as described below in the search process. We found that 271studies utilized a single method, whereas 180 studies utilized integrated methods. Data envelopment analysis (DEA) was the most common, used by 97 studies. However, an analytic hierarchy process (AHP) was utilized by 178 studies when counting both simple and integrated methods. It was shown that single methods were more commonly used in education, environment, health, and public services, and integrated methods were relatively favored in economics/finance, energy, site selection, and waste management. We conclude that multiple decision-making methods are used in the public sector, and during2010–2020, there has been a tendency to use unified methods in decision-making processes.